Analysis of the Effect of Afval Material Composition on the Quality of Polyvinyl Chloride (PVC) Bottle Packaging in the Extrusion Blow Molding Process: Analysis of the Effect of Afval Material Composition on the Quality of Polyvinyl Chloride (PVC) Bottle Packaging in the Extrusion Blow Molding Process - Devita Sari (P3M Politeknik Negeri Media Kreatif, 2026)
PVC bottle packaging is an important product in the packaging industry. In an effort to improve efficiency and sustainability, the use of recycled materials (afval) as a mixture is increasingly being considered. This study aims to analyze the effect of afval composition on the quality of PVC bottle products, especially visual defects in the form of black spots, using the Statistical Process Control (SPC) and linear regression methods. The study was conducted at PT. X (disguised), with six variations of afval composition (0%, 10%, 20%, 30%, 40%, and 50%) and 300 samples. The results showed that the higher the afval composition, the greater the number of black spots that appeared. The results of linear regression showed the highest R² value of 0.959 at a composition of 50%, indicating a very strong correlation. The maximum afval composition recommended to keep product quality within tolerance limits is below 30%. Keywords : Afval, Extrusion Blow Molding, Black Spot, Quality Control, SPC